The impact of information system on general banking and foreign exchange a case for Al Arafah Islami Bank - Chodhowry, Zunaid Kashem (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.